Cerebral revascularization with superficial temporal – middle cerebral artery anastomosis for complete carotid occlusion: An emerging modality for preventing recurrent stroke - Roopesh Kumar, V. R. (Medknow Publications & Media Pvt Ltd, 2013)
Complete long segment carotid occlusion presents a treatment challenge. These patients cannot be managed adequately by endarterectomy or stenting. Despite best medical management, many continue to develop recurrent strokes. In this select group of patients, there may be role for flow augmentation techniques like superficial temporal-middle cerebral artery bypass. We report a patient who was thus successfully treated and remains asymptomatic. The relevant literature is reviewed.